Demography, clinical features, and outcome of fungal keratitis presenting in tertiary eye care in Nepal - Bajracharya, Leena; Bade, Asta Ram; Gurung, Reeta (Asian Journal of Medical Sciences, 2023)
Background: Fungal keratitis is an important cause of ocular morbidity in developing countries. Aims and Objectives: To study fungal keratitis in detail along with its outcome. Materials and Methods: This is a retrospective study of fungal keratitis that had presented between October 2013 and March 2015. Results: 168 fungal ulcers were enrolled. 145 had fungus isolated in the culture; 23 had fungal elements seen only in potassium hydroxide mount examination. The average age of patients was 46.7 years. 55.3% were male. 75% were farmers. Patients presented at an average of 23.6 days since the onset of symptoms. In 85 cases (50.6%), trauma was the risk factor followed by steroid use (12.5%, n=21) and diabetes mellitus (7.7%, n=13). 72 out of 85 cases of trauma were due to vegetative matter. 94 (55.9%) ulcers had hypopyon. 56 (33.3%) ulcers had infiltrate size of ≥¼ of corneal surface. 12 (7.1%) ulcers were perforated at presentation. Out of 145 fungal isolates, Aspergillus species and Fusarium species were isolated in equal numbers (n=41, 28.3% each), followed by unidentified hyaline fungus (14.4%, n=21). The ulcers were treated with combination of topical natamycin 5% and fluconazole 0.3% with or without oral fluconazole. 111 (66.1%) fungal ulcers improved with medical treatment, 37 (n=22.0%) underwent therapeutic penetrating keratoplasty, 6 (3.6%) were eviscerated and outcome unknown in 14 (8.3%). Smaller-sized ulcers, ulcers without hypopyon and those presenting within 7 days had better prognosis (>80% healing with medical treatment) with statistical significance. Conclusion: Farmers were constantly at risk of fungal keratitis due to work-related trauma. Fungal ulcers presented late with large sized ulcers and with complications, thus making treatment challenging and necessitating surgical intervention. Timely treatment had better prognosis.